On the Million-degree Signature of Spicules - Souvik Bose; Jayant Joshi; Paola Testa; Bart De Pontieu (The Astrophysical Journal Letters)
Spicules have often been proposed as substantial contributors toward the mass and energy balance of the solar corona. While their transition region (TR) counterpart has unequivocally been established over the past decade, the observations concerning the coronal contribution of spicules have often been contested. This is mainly attributed to the lack of adequate coordinated observations, their small spatial scales, highly dynamic nature, and complex multithermal evolution, which are often observed at the limit of our current observational facilities. Therefore, it remains unclear how much heating occurs in association with spicules to coronal temperatures. In this study, we use coordinated high-resolution observations of the solar chromosphere, TR, and corona of a quiet-Sun region and a coronal hole with the Interface Region Imaging Spectrograph (IRIS) and the Atmospheric Imaging Assembly (AIA) to investigate the (lower) coronal (∼1 MK) emission associated with spicules. We perform differential emission measure analysis on the AIA passbands using basis pursuit and a newly developed technique based on Tikhonov regularization to probe the thermal structure of the spicular environment at coronal temperatures. We find that the emission measure (EM) maps at 1 MK reveal the presence of ubiquitous, small-scale jets with a clear spatiotemporal coherence with the spicules observed in the IRIS/TR passband. Detailed spacetime analysis of the chromospheric, TR, and EM maps show unambiguous evidence of rapidly outward-propagating spicules with strong emission (2–3 times higher than the background) at 1 MK. Our findings are consistent with previously reported MHD simulations that show heating to coronal temperatures associated with spicules.